San Marino : Staff Report of the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
San Marino showed enviable growth performance. Despite the positive economic developments, the central government budgetary balance has moved into a substantial deficit on an accruals basis, because of tax collection difficulties and rapidly rising outlays on generous entitlement programs. Executive Directors noted that reforms of the pension and health care systems were required to maintain the country's sound fiscal position. They welcomed the authorities' plans to strengthen banking supervision, adopt a legal framework to fight against money laundering, and improve statistics and accounting.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet